2012
DOI: 10.1167/iovs.11-9280
|View full text |Cite
|
Sign up to set email alerts
|

Different Subsets of Tumor-Infiltrating Lymphocytes Correlate with Macrophage Influx and Monosomy 3 in Uveal Melanoma

Abstract: All studied subtypes of tumor-infiltrating immune cells were collectively increased and showed an association with monosomy of chromosome 3 suggesting that tumor intrinsic factors control the leukocyte influx, possibly through local chemokine secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 40 publications
9
109
0
1
Order By: Relevance
“…We recently observed that both CCL22 and CCL2 were expressed in freshly cultured uveal melanoma cells as well as in monocytes. 33 Furthermore, we observed that increased numbers of TAMs and lymphocytes, as well as HLA expression, were all associated with chromosome 3 loss (Figure 3). There is evidence that chromosome 3 is associated with an increased leukocyte population, but the molecules involved have not yet been identified.…”
Section: Soluble Mediators: Cytokines and Chemokinesmentioning
confidence: 83%
See 1 more Smart Citation
“…We recently observed that both CCL22 and CCL2 were expressed in freshly cultured uveal melanoma cells as well as in monocytes. 33 Furthermore, we observed that increased numbers of TAMs and lymphocytes, as well as HLA expression, were all associated with chromosome 3 loss (Figure 3). There is evidence that chromosome 3 is associated with an increased leukocyte population, but the molecules involved have not yet been identified.…”
Section: Soluble Mediators: Cytokines and Chemokinesmentioning
confidence: 83%
“…The predominant cells are CD8 þ CTLs with a weaker presence of CD4 þ cells and also CD3 þ FoxP3 þ Tregs. 33 The number of infiltrating CD163 þ M2 macrophages is related to the number of Tregs, but it is not clear whether these cells interact. Different types of tumour-infiltrating leukocytes can affect each other's function.…”
Section: T Cellsmentioning
confidence: 99%
“…These factors suppress T cell proliferation and effector function, and could induce immunosuppressive regulatory T (Treg) cells. + M2 macrophages [7,8] . Infiltration of immune cells occurs more frequently in epithelioid-celltype UM.…”
Section: Immunological Microenvironment Of Primary Uveal Melanomamentioning
confidence: 99%
“…It has been reported that Treg cells are recruited into tumors by chemokines, CCL17 and CCL22 that are produced by M2 macrophages. Furthermore, tumor-produced CCL2 and CCL22 have a role not only in attracting tumor-promoting macrophages, but also in promoting their survival and M2 polarization [7] . While UM cells possess tumor-associated antigens and tumor-infiltrating CD4 + and CD8 + cells are present in the primary UM, Treg cells are also present in the tumor.…”
Section: Immunological Microenvironment Of Primary Uveal Melanomamentioning
confidence: 99%
“…Studies in mice revealed that depletion of macrophages during tumor induction prevented tumor growth, whereas in non-depleted mice all animals developed ocular tumors [116][117][118]. Next to TAMs in uveal melanoma CD8+ T-cells and CD3+FoxP3+ regulatory T-cells (Tregs) have been detected [119]. Tregs modulate other immune cells toward a tolerance state and high numbers of Tregs are associated with a poor prognosis [120].…”
Section: The Role Of Lymphangiogenesis In the Tumor Microenvironment mentioning
confidence: 99%